AQCHADARYA BASIN AND LOWER ZARAFSHAN VALLEY RESIDENTS JEWELRY ART HISTORY PAGE (TAMADDUN NURI JURNALI, 2024)
The article analyzes the history of jewelry art of the Khorezm Oasis Aqchadarya tributary and the Neolithic inhabitants of the lower Zarafshan Valley.